The Thirty Years of Indonesian Sharia Banking: Potential, Prospects and Challenges in the Era of Technological Disruption - Indupurnahayu Indupurnahayu; Yusuf Amri; Bramastyo Bontas Prastowo; Abrista Devi (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
In the contemporary Indonesian economy, banks serve as fundamental financial institutions that play a pivotal role in shaping economic activity, influencing income distribution, and maintaining price stability. The introduction of sharia banking in 1992 was largely driven by concerns within the Muslim community regarding the permissibility of interest (riba) under Islamic law. As a result, sharia banking emerged as an alternative financial system that aligns with Islamic principles, offering interest-free banking solutions. This study provides a comprehensive descriptive analysis of Indonesia's regulatory and legal preparedness in supporting the growth and sustainability of sharia banking institutions over the past three decades. It examines key factors such as economic potential, the availability of skilled human resources, and disparities in asset accumulation between conventional and sharia banks. Additionally, this research assesses the significant developments in the sharia banking sector over the past five years, highlighting key achievements, policy advancements, and institutional reforms aimed at enhancing financial inclusion and competitiveness. Furthermore, the study explores the prospects and challenges of sharia banking in the era of technological disruption. The rapid evolution of digital financial services, fintech integration, and regulatory advancements have created both opportunities and obstacles for the sector. While technology facilitates greater accessibility and operational efficiency, it also poses challenges related to cybersecurity, regulatory adaptation, and market competition. By analyzing these dynamics, this research aims to provide valuable insights into the future trajectory of sharia banking in Indonesia and its potential contributions to a more inclusive and resilient financial system.   Keywords: Sharia banking, Islamic finance, regulatory framework, economic potential, technological disruption